'Girls Don't Become Craftsmen': Determinants and Experiences of Children's Work in Gemstone Polishing in Jaipur. Issue 4 (3rd April 2017) - Ghorpade, Yashodhan
Abstract : This paper explores the determinants and valuations of children's work and schooling choices drawing on primary mixed-methods research in the gemstone polishing industry of Jaipur, India. In addition to economic and demographic factors, the gendered expectations of children's futures shapes their work and schooling outcomes. For boys, work is additionally driven by the need to acquire training for future employment and wages, and simultaneously complements, and competes with formal schooling. They can work at workshops, acquire higher skills, and can aspire to become skilled craftsmen whereas girls work at home on low-skill activities mainly to supplement household income.